Document reproduction in libraries - Mason, Donald; Association of Assistant Librarians (London : Association of Assistant Librarians, 1968)
This book endeavours to present to students of librarianship an outline of the major aspects of documentation services in libraries, and restricts itself in the main to those processes which are available commercially.
Includes index.
Includes bibliographical references: p.144.
aia 03/04/2018
Loans
Keywords: Copying processes